Pemanfaatan Limbah Galon Sebagai Wadah Budidaya Ikan dan Tanaman (Budikdamlon) Sebagai Langkah Pengelolaan Sampah Anorganik di Dusun Jombor, Desa Jetis, Kecamatan Bandungan, Kabupaten Semarang, Jawa Tengah - Luthfi Abdurrohim; Maulina Eril Suprapto; Galuh Adi Insani (Direktorat Pengabdian kepada Masyarakat, 2024)
The increase in population growth correlates with a rise in environmental pollution from domestic garbage. Waste constitutes an environmental issue encountered by multiple areas in Indonesia, including Jombor, Jetis Village, Bandungan District, Semarang Regency, Central Java. It is essential to transform trash, particularly inorganic waste, into usable products to mitigate environmental contamination. The Jombor Farmers and Livestock Group's Budikdamlon initiative seeks to enhance the use and value of inorganic waste by implementing a labor program that transforms it into tiny horticulture containers measured in gallons. The execution of the work program utilized the pre-test approach, content presentation, and demonstration of budikdamlon creation, and concluded with a post-test to assess the enhancement of the target audience's comprehension. A 12.9-point difference from the mean between the pre-test and post-test provided evidence of a significant increase in knowledge, according to the study's findings. The socializing and demonstration program was considered effective in elucidating waste processing through its application in small horticulture containers, with the expectation that the target audience will use it in their daily lives to fulfill household food requirements.